Partners in learning: Redefining mentorship for a learning organization - Jonathan Cook; Mandia Adonisi; Conrad Viedge (South African Journal of Business Management, 1994)
Mentorship programmes are popular for the development of black managers in South Africa. In the literature, controversy surrounds attempts to institutionalize mentorship. In this article it is argued that the concept of a learning partnership should replace that of mentorship, particularly in what are seen to be learning organizations. Many mentorship programmes are predicated on the belief that a warm and caring relationship is a prerequisite for effective development of protégés. Redefining the desired relationship as a learning partnership removes this demand on the relationship and places it squarely in the confines of a normal business affiliation in which the focus is mutual learning. Essential to the process of black advancement is empowerment. There are a number of dimensions to empowerment. In this article three key dimensions are discussed in relation to the development of black managers, namely objective power, subjective power and empowerment in competence. Based on insights gained in the initial phases of a mentorship programme implemented in a leading information technology company, a number of principles are offered for implementing learning partnerships in a learning organization. These revolve around the need to use a new paradigm to interpret the learning experiences that constitute a developmental relationship between a young and promising employee and a more experienced and knowledgeable manager.
Keywords: 650